The Awareness of plagiarism among university teachers in Sri Lankan Universities - Athukorala A.W.V (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2025)
Purpose. This study explores the awareness of plagiarism among university lecturers in Sri Lanka, with particular relevance to the field of library and information science. It highlights the crucial role of information literacy in addressing plagiarism in academic settings. As academic dishonesty, especially plagiarism, continues to rise, understanding faculty awareness is essential for fostering academic integrity and designing effective prevention strategies. Methodology. A quantitative approach was used, employing an online questionnaire distributed to academics from 17 Sri Lankan universities. A convenience sampling technique selected 104 respondents. Data were analyzed using SPSS through descriptive statistics and Pearson Chi-Square tests to examine relationships between variables. Results and Discussions. About 55.3% of respondents reported clear definitions of plagiarism within their departments, while 22.3% indicated uncertainty or lack of clarity. Most participants (95.2%) discussed plagiarism with students, though awareness varied by academic field. Faculties of aesthetics and commerce showed greater participation in awareness programs than engineering and technology. Additionally, 60.58% of respondents said their institutions used plagiarism detection software. Conclusion. The study indicates generally positive awareness of plagiarism among Sri Lankan university lecturers, but notable gaps exist in some academic areas. The adoption of detection software is a significant step, yet there remains a need for better training and targeted awareness efforts tailored to faculty needs. This research contributes to discussions on academic integrity and emphasizes the importance of continuous education and institutional commitment to preventing plagiarism in higher education.